PEMETAAN POTENSI MATAAIR DI PULAU BALI - Noorhadi Rahardjo (BPPT)
There are three objectives of this research. First, to map springs location, second to know spring characteristic and third to calculat springs potency for domestic use. To reach these aims, springs location were plotted on map base on its coordinate. Springs characteristic were analysed descriptively by spatial analysis base on geologic, geomorphologic and hydrogeologic conditions. Springs potency were calculated base on its discharge, whereas domestic use was determined 60 l/person/day for rural and 120 l/person/day for urban area. The study shows, that springs distribution in Bali Island are not homogeny Springs appearance were controlled by geologic structure as fault and rock contact. The differences of discharge also depend on the structure. Contact between volcanic rock (tuff and lahar) from Buyan-Bratan-Batur Formations with another rock formation in its surrounding result many springs appereance with high discharge. Beside that, orohydrology properties of Agung Mount as strato volcanic result springs belt in a certain elevation and each slope changing. Base on calculation, springs potency in Bali Island are 628.800 m3/month,whereas the domestic use is 9.079.990 m3/month. So, the springs potency is just 6,9% from domestic use in Bali Island.Key words : springs potency, springs distribution, springs characteristic